CANTHARANTHUS ROSEUS LEAF EXTRACT ACCELERATES HEALING OF WOUND WISTAR RAT - Anom-Dada, I K.; Berata, I K.; Putra-Manuaba, I. B.; Damriyasa, and I M. (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES, 2013)
Cantharantus roseus (C. roseus) is a medical plant that has been used to treat various diseases. This study was carried to determine C. roseus leaf extract able to acclerate wound healing in Wistar rat. Full skin-tickness round wounds were created on the back of the rats. Wound healing was evaluated after treated with 15% of a mixture of leaf extract of C. roseus and vaseline. The rats were divided into two groups, each group consist of 16 rats. Wound healing was assesed in five and fifteen days after treatment by measuring wound area, wound closure, and counting the new capillary vessel number (angiogenesis). The result of the study indicated that extract of C. roseus leaf accelerates the wound healing in Wistar rat. Coverage rate of wound is faster on treated group than control group ( p <0.05). Wound closure and angiogenesis in early wound healing were higher in treated group than control group ( p <0.05). These results suggested that the first phase of wound healing was shortened, and the proliferative and maturation phases were advanced by methanol extract of C. roseus leaf. Therefore, it can be concluded that C. roseus could be potential to help in topical management of wound healing.
Keywords: C. roseus, wound, healing, collagenesis, angiogenesis.